RESPON PERTUMBUHAN DAN PRODUKSI TANAMAN JAGUNG PULUT TERHADAP PERLAKUAN PRUNING TONGKOL KEDUA DAN PENYEMPROTAN PUPUK PELENGKAP CAIR - Edy, Edy; Tjoneng, Amir; Subaedah, St.; Rahman, Anita; Alimuddin, Suraedah (AGROTEK: Jurnal Ilmiah Ilmu Pertanian, 2024)
This study was conducted to determine the response of corn plants to the second cob pruning treatment and liquid complementary fertilizer (LCF) spraying on the Growth and Production of Waxy Corn Plants (Zea mays ceratina L.). This study was conducted at the Experimental Garden of Pabentengan Bajeng Village, Gowa Regency, South Sulawesi, from September to December 2018. The materials used in this study were local waxy corn seeds, liquid complementary fertilizer (Bram Evolution) urea and NPK fertilizer. The Split Plot Design method was used. The main plot is without pruning and with pruning, while the sub-plot is Spraying Liquid Complementary Fertilizer (LCF) consisting of 4 levels, namely without LCF spraying, spraying with a concentration of 10 mL/L water, 20 mL/L water, and 30 mL/L water, 8 treatment combinations repeated 3 times to obtain 24 experimental units. The results of this study indicate that pruning the second cob increases the dry weight of the plant, seed weight per plant, seed weight per plot, and seed weight per hectare. LCF spraying and the interaction between pruning and LCF spraying treatments did not affect the observed parameters